Geotechnology applied to land classification in areas of the Atlantic Forest in southeastern Brazil (Research, Society and Development, 2021)
The objective of this study was to classify the lands of a micro-watershed located in the Atlantic forest biome, in a region of rough relief, in the use capacity system using geotechnology resources and indicate uses for the lands according to their suitability. The theoretical basis of the Manual for Utilitarian Survey and Classification of Land in the Use Capacity System with adaptations for areas of rough relief was adopted. The study was carried out from the survey of topographic information to construct the altimetric map of the watershed, followed by the survey of the physical environment, especially water erosion, description of soil profiles and collection of samples. The parameters effective depth, texture, permeability, slope, erosion, fertility, and land use were evaluated. Based on the pedological data and on the use of applied geotechnology, the soil map was created, and the lands of the watershed were classified and mapped in the use capacity system. After interpretation of the survey products, it was verified that in rough relief, slope is the predominant factor to determine the classes of land use, as it outweighs the other parameters evaluated. Land classification land with the use capacity system promotes optimization in the use of areas with agricultural areas and preservation of those destined for conservation.